(3hajGJ GdCYjGf hCfHGA CHfGA GdReGfs - (3GHf NdcGf , CMeO Hf eMeO Hf EHQGgje Hf CHj HcQ GdHQecj GdGQHdj, TeS GdOjf CHh GdYHGS,J (B681 (3g` s ((3LeGd GdOjf GdCSfhi s)
(3BNQgG (B:s
(3jfJgi HJQLeI GdYdGA Hf Ydi Hf GdShGOi s
(3Yf fSNI HNW GdeDdas
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B220 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B59s
Keywords: (3GdJGQjNs